Effect of different mixing methods on the bacterial microleakage of white Portland cement and white Mineral Trioxide Aggregate - Shahriar Shahi; Asmar Bashirzadeh; Hamid Reza Yavari; Farnaz Jafari; Amin Salem Milani; Negin Ghasemi; Mohammad Samiei (Tabriz University of Medical Sciences, 2017)
Background. The aim of this study was to investigate the effect of different mixing methods (ultrasonic, amalgamator, and conventional) on the bacterial microleakage of white Portland cement (WPC) and white MTA (Tooth-colored Formula, Dentsply, Tulsa Dental, Tulsa, OK). Methods. A hundred human single-rooted permanent teeth were decoronated to obtain 14 mm of root length in all the samples. The root canals were cleaned, shaped and obturated. Three millimeters of each root apex were cut off and randomly divided into 6 groups of 15 each (3 groups for WMTA and 3 groups for WPC, each with 3 different mixing methods) and 2 positive and negative control groups (each containing 5 samples). Brain-heart infusion agar (BHI) suspension containing the bacterial species Enterococcus faecalis (ATCC 29212) was used for leakage assessment. Statistical analysis was carried out using descriptive statistics and Kaplan Mayer survival analysis with censored data and log rank test using SPSS 18. Statistical significance was set at P<0.05. Results. The survival means in PC for conventional method, amalgamator, and ultrasonic were 80.2±13.64, 78.5±13.46 and 84.667±11.42 days, with 49.13±12.96, 66±13.32 and 69.07±11.5 days for MTA, respectively. The log rank test showed no significant differences between the three methods in each material (P>0.05). Conclusion. Bacterial microleakage in the studied samples was not significantly different in terms of the type of the mixing method.